Citric acid promotes disulfide bond formation of whey protein isolate in non-acidic aqueous system. (15th February 2021) - Li, Tong; Hu, Jialun; Tian, Ran; Wang, Kaili; Li, Jinpeng; Qayum, Abdul; Bilawal, Akhunzada; Gantumur, Munkh-Amgalan; Jiang, Zhanmei; Hou, Juncai
Highlights: Citric acid (CA) promoted disulfide bond formation of whey proteins at non-acidic pH. Free SH groups of whey protein isolate (WPI)-CA decreased as a function of CA. Alteration in secondary and tertiary structures of CA-treated WPI occurred. Abstract: Impacts of citric acid (CA) treatment under non-acidic conditions (pH 7.0, 8.0 and 9.0) on whey protein isolate (WPI) were examined in this study. Size exclusion chromatography and SDS-PAGE indicated that molecular size and weight of WPI-CA became larger at pH 7.0, 8.0 and 9.0 with CA ranged from 0 to 15 mg/mL, but the protein aggregates disappeared after β-mercaptoethanol was added. The free SH groups of WPI-CA gradually decreased. This could be deduced that CA could promote disulfide bond formation of WPI at the non-acidic pH values. Furthermore, fourier transform infra-red (FTIR) spectroscopy and fluorescence spectroscopy data confirmed the conformational changes of secondary and tertiary structures of CA-modified WPI, respectively. Therefore, these results suggested that disulfide bond formation of WPI occurred at citric acid treatment under non-acidic conditions, being contributed to production of its larger molecular size substances and alteration of its structural characteristics.